Fatty acid composition and tocopherol content of processed marine fish and contribution of omega-3 fatty acids - Devadason, Chandravathany; Jayasinghe, C. V. L.; Sivaganehsan, R.; Gotoh, Naohiro (Indian Journal of Fisheries, 2019)
The present study analysed fatty acid composition and tocopherol content of raw, curried and fried fish. Of the saturated fatty acids, C12:0, C14:0 and C16:0 had significant increase in fried and curried fish than raw fish. Of monounsaturated fatty acids, C18:19c significantly increased in fried and cooked form whereas polyunsaturated fatty acids, C20: 5n3 (EPA) and C22:6n3 (DHA) showed significant decrease in fried and curried fish. In cooked and fried fish there was significant reduction of tocopherol content. There was increase in hypocholesterolaemic and hypercholesterolaemic fatty acid (HH) ratio in fried and curried fish. Fish fried in coconut oil and fish curry in coconut cream were not found to be healthy processing methods and both processing methods lead to significant reduction in potential health benefits of omega-3 fatty acids in the fishes.